Effect of dry and wet finishing and polishing on color change and opacity of nanofill and nanohybrid composites - Mehdi Molaei; Anoosh Mohammadzadeh; Amir Ghasemi; Mehdi Badiee (BMC, 2024)
Abstract Background As superior esthetic is one of the main reasons for using composite resins, it is very important to be familiar with factors and techniques affecting their optical properties and appearance. Aim The aim of this study was comparing the effect of finishing and polishing with and without water coolant, on the color change and opacity of composite resin materials. Methods Composites used for preparing samples were Z250 (microhybrid), Z350XT (nanofilled), and Z550 (nanohybrid). Then divided into 4 groups of 5 depending on finishing and polishing technique (dry or wet) and time (immediate and after twenty-four hours). After polishing, samples were assessed using a spectrophotometer. Color change and opacity were determined. Data was analyzed using Kolmogorov-Smirnov, ANOVA and Tukey HSD tests. Results Type of material at both time had a significant effect on ΔE and opacity. Our results in dry and wet technique immediately(T0) showed that the highest and lowest ΔE and opacity belong to Z350XT (p < 0.001). After Twenty-four hours (T24), opacity of Z250 in wet condition was higher than dry condition (p < 0.001). Conclusions Wet or dry technique was only effective on color in immediate polishing. Regarding opacity, technique was only effective in case of delayed polishing.